2016
DOI: 10.1055/s-0042-116487
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the white opaque substance within colorectal neoplastic epithelium as visualized by magnifying endoscopy with narrow-band imaging

Abstract: Background and study aims: We previously reported our discovery of a white opaque substance (WOS) that is opaque to endoscopic light inside the epithelium while using magnifying endoscopy (ME) to examine gastric epithelial neoplasia. Histopathologic analysis revealed that the WOS comprises minute lipid droplets (LDs) accumulated within the neoplastic epithelium. In addition, the WOS was found in colorectal epithelial neoplasia, although it was unclear whether this WOS corresponded to an accumulation of LDs, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…WOS was more frequently present in carcinomas (66.0%) than in adenomas (31.8%), and more frequent in SM carcinomas (75.9%) than in Tis carcinomas (59.0%). Thus, the presence of WOS is an indication of carcinoma …”
Section: Discussion Topics Of the Jges Core Sessionsmentioning
confidence: 99%
See 1 more Smart Citation
“…WOS was more frequently present in carcinomas (66.0%) than in adenomas (31.8%), and more frequent in SM carcinomas (75.9%) than in Tis carcinomas (59.0%). Thus, the presence of WOS is an indication of carcinoma …”
Section: Discussion Topics Of the Jges Core Sessionsmentioning
confidence: 99%
“…Thus, the presence of WOS is an indication of carcinoma. 15 Blue laser imaging (BLI) was the second most discussed topic among the lectures. It is an IEE technique that uses the laser-based endoscope system.…”
Section: Discussion Topics Of the Jges Core Sessionsmentioning
confidence: 99%
“…Only a single clinicopathologic study that evaluated WOS in colorectal neoplasms has been published[ 7 ]. In that study, Imamura et al[ 7 ] reported that 19 (47.5%) of 40 colorectal lesions with WOS were positive for oil red O staining, while only 5 (5%) of 40 colorectal lesions without WOS were positive. Moreover, the investigators reported that 40 (100%) of 40 colorectal lesions with WOS were positive for adipophilin, while 25 (62.5%) of 40 colorectal lesions without WOS were positive.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid staining for gastric and duodenal epithelial neoplasms has demonstrated that most gastric neoplasms with WOS are positive for oil red O staining[ 6 ], and the distribution of Sudan IV-positive lipid droplets corresponds approximately with that of WOS in duodenal neoplasms[ 3 ]. To date, however, only a single study investigated the histopathological features of WOS in colorectal epithelial neoplasms[ 7 ]. In that study, Imamura et al[ 7 ] reported that WOS in colorectal epithelial neoplasms was composed of lipid droplets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation